INFLUENCE CHRONICKIDNEYDISEASEPROGRESSES TO QUALITYOFLIFE - Krasiuk, I. V. (Ukrainian Journal of Nephrology and Dialysis, 2014)
Aim. To determine the characteristics of quality of life in patients with chronic kidney disease (CKD ) II–Vst. Methods. 171 patients with CKD II–IVst, except for routine clinical and laboratory examinations, have been studied the quality of life (QOL) using a questionnaire assessing quality of life SF– 36. Results. It was found most of the QOL was significantly worse with the progression of CKD. Total QOL indicators and indicator “effect of kidney disease”. most significantly reduced. Correlation most QOL with age, hemoglobin, blood pressure levels was revealed. Conclusions. QOL decrease with the progression of CKD. Age, hemoglobin level, blood pressure affect QOL.